Indonesia EXECUTION ANALYSIS OF FIDUCIARY WARRANTIES REGISTERED: EXECUTION ANALYSIS OF FIDUCIARY WARRANTIES REGISTERED - Siagian, Mangihut Tua (LPPM Universitas Putera Batam, 2021)
Fiduciary as an agreement to follow the principal agreement of the parties to fulfill the achievements. If the execution process is not accompanied by a deed, the executor will show the court's decision. The formulation of the problem of how the debtor carries out the execution of the fiduciary guarantee that is not registered and what the legal consequences are for the execution of the collateral object under hand. However, with the aim of knowing the execution of the fidusion guarantee that is not registered. The research method uses a normative review / literature review which is descriptive analytical in nature. The results of the research are contained in a conclusion which shows that the execution can be carried out if there is a credit problem. If the guarantee is not made under hand and has not been registered according to statutory provisions, it will not have executorial power. The main factor is not registering it because of the high cost that causes the debtor not to register the Fiduciary Guarantee. In terms of its implementation, the community becomes more aware of the ins and outs, their rights and the consequences of taking credit using the fiduciary system